Pengaruh Keragaman Produk dan Kualitas Pelayanan terhadap Kepuasan Pelanggan di Apotek Kimia Farma - Khomsah Kamilah; Alfin Adam; Resti Rohayati; Nazwa Awlia Maulana; Rismawati Rismawati; Fatimah Azzahra; Ramadhani Ramadhani; Endang Silaningsih (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the effect of product diversity and service quality on consumer satisfaction at Kimia Farma Pharmacy. Product diversity includes the variety of types of drugs, health products, and medical needs available, while service quality includes the speed, compassion, and accuracy of service provided by Kimia Farma pharmacy staff. Data were collected through questionnaires distributed to Kimia Farma Pharmacy consumers using quantitative methods. Data analysis was carried out using multiple linear regression to identify the effect of each variable on consumer satisfaction. The results of the study indicate that product diversity and service quality have a positive and significant effect on consumer satisfaction. This explains that improving product and service quality can increase the level of consumer satisfaction. These findings have an impact on Kimia Farma Pharmacy management to continue to improve service quality and expand product diversity in order to optimally meet consumer needs. In addition, this study also contributes to the pharmacy business development strategy amidst increasingly tight pharmaceutical industry competition, especially in designing a customer-oriented approach. Further research can examine other variables such as price, location, or consumer loyalty to expand understanding of the factors that influence customer satisfaction more comprehensively.